Gender imagery in Philippine psychology a critique of the literature. [article]. - Torres, Amaryllis Tiglao
This study endeavored to describe and interpret the the existing literature of sex and gender differences found in the PJP and a few other Philippine publications over the past twenty years. The review revealed that while some stereotypic beliefs about masculinity and femininity are not described by actual studies, the domestication of women remains a dominant orientation among Filipino men and women. These findings were reinterpreted in terms of gender-fair perspectives. Substantive and methodological gaps in research related to gender studies were pointed out.